T1 Vertebra Pedicular Osteoid Osteoma: Minimally Invasive Surgical Resection Aided by New Integrated Navigation to 3D Imaging Device - M. Prod’homme; G. Cavalié; G. Kerschbaumer; S. Valmary-Degano; M. Boudissa; J. Tonetti (Case Reports in Orthopedics)
We hereby describe a minimally invasive resection of a T1 pedicular osteoid osteoma next to the vertebral canal. The patient had an 18-month report of painful radiculopathy. We performed the surgery under 3D imaging guidance using navigation with an all-in-one device. Full procedure irradiation was 1.17 mSv for a 181-picture acquisition. Complete operative time incision to closure was 58 minutes. Despite sparing the vertebral stability without any fixation, the tumor resection was well-margined, thanks to the focused guidance. After surgery, the patient had complete relief of his symptoms at the 6-month follow-up. 3D imaging system coupled to navigation made the procedure safe without consuming time. The single Surgivisio® device allows comfortable 3D minimally invasive spine navigation surgery with the ergonomics of a C-arm.